How to Conduct Responsible Research: A Guide for Graduate Students. Issue 3 (19th March 2021) - Antes, Alison L.; Maggi, Leonard B.
Abstract: Researchers must conduct research responsibly for it to have an impact and to safeguard trust in science. Essential responsibilities of researchers include using rigorous, reproducible research methods, reporting findings in a trustworthy manner, and giving the researchers who contributed appropriate authorship credit. This "how‐to" guide covers strategies and practices for doing reproducible research and being a responsible author. The article also covers how to utilize decision‐making strategies when uncertain about the best way to proceed in a challenging situation. The advice focuses especially on graduate students, but is appropriate for undergraduates and experienced researchers. It begins with an overview of responsible conduct of research, research misconduct, and ethical behavior in the scientific workplace. The takeaway message is that responsible conduct of research requires a thoughtful approach to doing research in order to ensure trustworthy results and conclusions, and that researchers receive fair credit. © 2021 Wiley Periodicals LLC.